Assessment of Barriers to Exclusive Breast Feeding Among Working Saudi Mothers - Albezrah, Nisreen Kh. Aref; Alshehri, Haneen Ali; Alswat, Raghad Hilal; Almalki, Manal Saeed; Al fuhayd, Atheer Mohammed; Alkenany, Reem Abdullah; Alswat, Shrooq Homood; Alzahrani, Khames T. (International Journal of Innovative Research in Medical Science, 2021)
Background: The World Health Organization and the United Nations International Children’s Fund recommend mothers to exclusively breastfeed their infants for the first six months of their life that should be initiated within the first hour after birth. Methods: This cross-sectional study included currently employed Saudi working mothers residing the Western region of Saudi Arabia. A self-administered questionnaire was distributed through email and social media. Each person meeting the inclusion criteria was provided informed consent, explaining the study aim, and ensuring the confidentiality of information. Data were obtained by filling out the designed Questionnaire. Result: This study included 692 working Saudi mothers. The frequency of exclusive breast feeding was 40.2%, which was continued by 29.8% only after returning to the work. Insufficient breast milk secretion (17.5%) and the lack or minimal support from the workplace for EBF (6.6%) were commonly stated by the mothers. There were great deficiencies in the breastfeeding friendly work policies including the absence of breast feeding or breast milk-pumping place (86.4%), absence of breastfeeding hours during work time (80.9%), and the presence of a strict full-time schedule that did not allow freely use of the nursing break. Conclusion: The present study shows low prevalence of exclusive breast feeding among working mothers in the Western region of Saudi Arabia. Multiple barriers to continuing breast feeding have been detected. Insufficient breast milk secretion and the lack of breastfeeding friendly work policies were common reasons.